Friends and strangers : the making of a Creole culture in colonial Pennsylvania - Smolenski, John (Early American studies., 2010)
Friends and Strangers offers a provocative new look at the transfer of English culture to North America. Setting Pennsylvania in the context of the broader Atlantic phenomenon of creolization, Smolenski's account of the Quaker colony's origins reveals the vital role this process played in creating early American society.